2022
DOI: 10.3389/fpls.2022.1023696
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolomic and transcriptomic analysis reveals the role of phenylpropanoid biosynthesis pathway in tomato roots during salt stress

Abstract: As global soil salinization continues to intensify, there is a need to enhance salt tolerance in crops. Understanding the molecular mechanisms of tomato (Solanum lycopersicum) roots’ adaptation to salt stress is of great significance to enhance its salt tolerance and promote its planting in saline soils. A combined analysis of the metabolome and transcriptome of S. lycopersicum roots under different periods of salt stress according to changes in phenotypic and root physiological indices revealed that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 146 publications
1
1
0
Order By: Relevance
“…For example, we find a protein cluster related to suberin biosynthesis (Figure 5C), which is consistent with suberin being reported to prevent root water loss (46,47). We also find phenylpropanoid biosynthetic proteins to be a large portion of Cluster 4 (Figure 5C), with their accumulation having been related to abiotic stress resistance in apple (48) and wheat (49).…”
Section: Data Independent Acquisition (Dia) With 3-cv Faimsprosupporting
confidence: 84%
“…For example, we find a protein cluster related to suberin biosynthesis (Figure 5C), which is consistent with suberin being reported to prevent root water loss (46,47). We also find phenylpropanoid biosynthetic proteins to be a large portion of Cluster 4 (Figure 5C), with their accumulation having been related to abiotic stress resistance in apple (48) and wheat (49).…”
Section: Data Independent Acquisition (Dia) With 3-cv Faimsprosupporting
confidence: 84%
“…Transcriptome and metabolomic analysis found that genes involved in the synthesis pathways of phenylpropanin, ferulic acid (FA), and spermidine (Spd) in tomatoes, especially transcription factors such as MYB, Dof, BPC, and AP2/ERF, were expressed under salt stress [67]. Combined transcriptome and metabolome analysis under watermelon salt stress showed that genes involved in phenylpropanin synthesis, hormone signaling, and carbohydrate synthesis pathways, as well as bHLH family transcription factors, played an important role in improving the salt tolerance of watermelon [68].…”
Section: Discussionmentioning
confidence: 99%